Early physical activity after concussion is associated with sleep quality but not dizziness among adolescent athletes - Smulligan, K. L.; Wingerson, M. J.; Little, C. C.; Wilson, J. C.; Howell, D. R. (Journal of Science and Medicine in Sport, 2023)
Objectives: To assess the association between early physical activity and post-concussion sleep quality, dizziness, and postural stability among adolescents with concussion compared to uninjured controls. Design: Cross-sectional. Methods: Adolescents ages 13-18 years assessed within 14 days post-concussion and uninjured controls. Those with concussion reported if they participated in physical activity between the concussion and assessment. Participants completed the Dizziness Handicap Inventory, Pittsburgh Sleep Quality Index, and single/dual-task tandem gait. Results: We enrolled 34 participants with concussion (early physical activity: n=10, age=15.8±1.6 years, 70% female; no physical activity: n=24, age=16.0±1.3 years, 50% female) and 21?uninjured controls (age=16.0±1.8 years, 48% female). Compared to controls, the no physical activity group reported worse sleep quality (Pittsburgh Sleep Quality Index: 3.8±2.7?vs8.0±4.9 points, p=0.002) and single-task tandem gait time (13.7±3.4vs21.2±8.1 s, p=0.0006), while the early physical activity group did not (Pittsburgh Sleep Quality Index: 3.8±2.7vs5.8±3.2 points, p=0.38; single-task tandem gait: 13.7±3.4vs19.0±5.7 s, p=0.08). Compared to controls, early/no physical activity groups reported worse dizziness (Dizziness Handicap Inventory: 2.0±3.4vs22.9±23.8vs27.4±19.2 points, p<0.0001). There were no significant between-group differences for dual-task tandem gait (24.1±8.0vs24.8±6.2vs26.6±7.3 s, p=0.57). Conclusions: The no physical activity group reported worse sleep quality and slower single-task tandem gait than controls, while both groups reported similar sleep quality and tandem gait. Early physical activity may promote sleep quality and postural stability, or early physical activity may be a function of improved sleep and postural stability after concussion.